Kajian aktivitas antioksidan dan sitotoksik ekstrak etil asetat daun jarak pagar (Jatropha curcas) - Rahman, Sudarman; Febrianto, Yahya; Citrariana, Shesanthi; Sulistia, Tiya; Alfanaar, Rokiy; Suprayogi, Thathit; Fatiqin, Awalul; Arsana, Mu’afa Purwa (Universitas Mataram, 2025)
Antioxidants are chemical substances that have the ability to protect body cells from damage caused by excessive oxidation reactions. One of the uses of antioxidants from natural materials is jarak pagar leaves (J. curcas). This study aims to determine the antioxidant and cytotoxic activity against shrimp larvae from ethyl acetate extract of J. curcas leaves. Ethyl acetate extract from J. curcas leaves was extracted using the soxhletation method. Phytochemical testing was carried out using the tube method, antioxidant testing using the DPPH method and cytotoxic using the BSLT method. The results of the research showed that J. curcas contained secondary metabolite compounds in the form of flavonoids and polyphenols, the antioxidant activity test of Ethyl acetate extract from J. curcas leaves and the comparison control (vitamin C) produced an IC50 of 71,79±0.35 ppm and 8.78±0.21 ppm, respectively. The cytotoxic test of the ethyl acetate extract of J. curcas leaves contains active compounds that are toxic to the shrimp larvae with an LC50 of 72.13 ppm (LC50≤1000 ppm). The most effective concentration in free radicals scavenging is 160 ppm. Based on the results obtained, the ethyl acetate extract of J. curcas showed strong antioxidant activity and potential as an anticancer agent.